2023
DOI: 10.1108/imds-11-2022-0726
|View full text |Cite
|
Sign up to set email alerts
|

Achieving carbon neutrality with smart supply chain management: a CE imperative for the petroleum industry

Abstract: PurposeWith refineries contributing 68% of CO2 emissions from stationary combustion sources alone, smart technologies and the circular economy (CE) model for resource loop optimization can be a solution for carbon neutrality, especially within petroleum. Thus, this study aims to explore energy conservation by green technology improvement as a CE strategy for resource loop optimization and digital incorporation to maximize reprocessing lead ability rate and carbon-neutral benefits.Design/methodology/approachA g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 78 publications
(109 reference statements)
0
4
0
Order By: Relevance
“…Smart technologies and circular economy (CE) models can be a solution for promoting carbon neutrality in the petroleum industry. By taking this perspective, Yousaf et al . (2023) study how to maximize the reprocessing lead capability rate and carbon-neutral benefits through green technology improvement.…”
Section: Accepted Papers In This Special Issuementioning
confidence: 99%
See 1 more Smart Citation
“…Smart technologies and circular economy (CE) models can be a solution for promoting carbon neutrality in the petroleum industry. By taking this perspective, Yousaf et al . (2023) study how to maximize the reprocessing lead capability rate and carbon-neutral benefits through green technology improvement.…”
Section: Accepted Papers In This Special Issuementioning
confidence: 99%
“…Smart technologies and circular economy (CE) models can be a solution for promoting carbon neutrality in the petroleum industry. By taking this perspective, Yousaf et al (2023) study how to maximize the reprocessing lead capability rate and carbon-neutral benefits through green technology improvement. A game theoretic approach with Stackelberg equilibrium is considered under government cap-and-trade regulation to stimulate green technology improvement.…”
Section: 4mentioning
confidence: 99%
“…Industry 4.0 technologies, such as IoT, AI, blockchain, and big data analytics, facilitate communication and collaboration among supply chain partners, leading to leaner and more efficient processes while reducing waste. By integrating digital solutions, smart supply chains become more flexible, agile, and responsive, driving efficiency and promoting circular economy strategies that lead to joint emission reduction decisions, improved profits, and better collaboration among all supply chain members for a multi-win outcome (Mishra, Singh, 2021;Gažová et al, 2022;Yousaf et al, 2023) Integrating lean and agile methodologies has been demonstrated to enhance a firm's performance by offering benefits such as increased efficiency, waste elimination, and rapid adaptation to diverse and unpredictable customer demands (Raji et al, 2021). The primary objective of implementing digital technologies, such as Industry 4.0, is to boost operational efficiency, leading to improved performance (Kohnova, Salajova, 2023).…”
Section: Entrepreneurship and Sustainability Issuesmentioning
confidence: 99%
“…DT also plays an important role in promoting the achievement of sustainable development goals (Bican and Brem, 2020; Ahvenniemi and Huovila, 2021; Yousaf et al ., 2023). As the largest carbon emitter in the world, China has set the “30–60 Plan” target.…”
Section: Introductionmentioning
confidence: 99%